Analysis of The Added Value of The Palm Sugar In Rambah District Rokan Hulu Regency - Jelianti Lubis; Evy Maharani; Shorea Khaswarina (Jambura Agribusiness Journal, 2022)
Sugar palm is a type of plant that has high economic value. Almost all parts of the palm plant can be utilized, from the roots to the male flower bunches that can produce sap. The sap obtained from sugar palm is processed into palm sugar. The palm sugar processing business aims to obtain added value. The purpose of this study was to analyze the added value of palm sugar in the Rambah District, Rokan Hulu Regency. This research was conducted for one month, namely in August 2021. The method used was a survey method, sampling was carried out using the census method as many as 16 craftsmen in Rambah District, Rokan Hulu Regency. Analysis of the data used is the Hayami Method. The results showed that the added value ratio obtained from palm sugar was 30.20% (medium ratio) which means that palm sugar still has added value so it is feasible to be developed. The craftsmen should continue to maintain the palm sugar agro-industry by continuing to cultivate palm plants, increase the amount of production, and maintain the quality of palm sugar. The government should provide assistance to craftsmen to develop their businesses by providing assistance in the form of capital and appropriate technology.